Comparative characteristics of clinical, laboratory and instrumental indicators in children with seasonal influenza depending on the virus strain - E. D. Kazantseva; A. G. Petrova; A. S. Vanyarkina; E. A. Novikova; E. V. Moskaleva; L. V. Rychkova (Acta Biomedica Scientifica, 2022)
Introduction. According to the literature, it is known that clinical signs and symptoms of influenza may differ depending on age, the state of the human immune system, the serotype of the virus and its virulence. Intoxication, catarrhal and hyperthermia are main symptoms of influenza, but the disease does not always proceed classically, it may hide under the mask of other infections.   The aim was to conduct a comparative analysis of clinical, laboratory and instrumental parameters in children with influenza A(H1N1) and A(H3N2).   Materials and methods. A single-stage retrospective comparative study was carried out with the participation of 96 children from 1 month of age up to 13 years old with a diagnosis of influenza, who were hospitalized at the Irkutsk Regional Infectious Clinical Hospital from December 2018 to January 2019. Clinical and laboratory features of the course of influenza in children were determined depending on a viral strain.   Results. The structure of morbidity: influenza A(H1N1) – 70 people (73 %), influenza A(H3N2) – 20 children (21 %), influenza A clinically unvaccinated – in 3 people (3 %), mixed viral infection influenza H1N1 + adenovirus infection – 2 cases (2 %), mixed viral infection H1N1 flu + RS-virus – 1 case (1 %). In the clinic of both strains of the virus, symptoms prevailed: runny nose, dry cough, fever, intoxication. Muscle pain and pharyngeal hyperemia were significantly more common in influenza A(H1N1), the duration of symptoms did not differ. Lymphocytosis was more often observed in influenza A(H1N1), monocytosis – in influenza A(H3N2) (р < 0.05). In 64 % of cases, patients with influenza A(H1N1) had a high leukocyte index of intoxication (odds ratio – 2.2).   Conclusion. The symptoms of different influenza A viral strains virus in children are the same, however, muscle pain and hyperemia of the pharynx prevails in children with influenza A(H1N1).